Mosses as indicators of atmospheric metal deposition in an industrial area of southern Brazil Musgos como indicadores da deposição atmosférica de metais em uma área industrial do sul do Brasil - Aline Correa Mazzoni; Rosane Lanzer; Juçara Bordin; Alois Schäfer; Ronaldo Wasum (Acta Botânica Brasílica, 2012)
Caxias do Sul hosts the second largest metal-mechanic pole in Brazil, which increases the risk of atmospheric contamination. With the aim of identifying species that might be useful as indicators of atmospheric deposition of metals, 15 species of mosses from an urban and a rural setting were analyzed and compared with specimens deposited at the Herbarium of the Universidade de Caxias do Sul. Metal concentrations (Zn, Ni, Cd, Cr, Cu and Pb) were determined using Atomic Absorption Spectrometry (AAS). The Mann-Whitney test indicated concentrations of Zn, Cu, Pb and Cr that were significantly different between the urban and rural areas. Additionally, Concentrations of Zn, Cd, Cu and Pb were significantly higher in recently collected samples. The species Thuidium tomentosum Besch., Sematophyllum subpinnatum (Brid.) E. Britton, Helicodontium capillare (Hedw.) A. Jaeger, Schlotheimia jamesonii (W.-Arnott) Brid. and Meteorium deppei (Hornsch. ex Müll. Hal.) Mitt. are potential biomonitors of atmospheric metal deposition. Caxias do Sul sedia o segundo maior pólo metal mecânico do Brasil, apresentando elevado risco de contaminação atmosférica. Com o objetivo de identificar espécies úteis como indicadoras da deposição atmosférica de metais, foram analisadas 15 espécies de musgos procedentes da zona urbana e da área rural e espécimens depositados no Herbário da Universidade de Caxias do Sul. Os metais (Zn, Ni, Cd, Cr, Cu e Pb) foram determinados por meio de Espectrometria de Absorção Atômica (AAS). O Teste de Mann-Whitney indicou diferenças significativas nas concentrações de Zn, Cu, Pb e Cr entre as áreas urbana e rural. Um aumento significativo na presença de Zn, Cd, Cu e Pb foi evidenciado nas amostras recentes. As espécies Thuidium tomentosum Besch., Sematophyllum subpinnatum (Brid.) E. Britton, Helicodontium capillare (Hedw.) A. Jaeger, Schlotheimia jamesonii (W.-Arnott) Brid. e Meteorium deppei (Hornsch. ex Müll. Hal.) Mitt. são indicadas como potenciais biomonitores da deposição atmosférica de metais.